2023
DOI: 10.1038/s41598-023-38673-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative thalamus volume is not associated with preoperative cognitive impairment (preCI) or postoperative cognitive dysfunction (POCD)

Abstract: A growing body of literature suggests the important role of the thalamus in cognition and neurodegenerative diseases. This study aims to elucidate whether the preoperative thalamic volume is associated with preoperative cognitive impairment (preCI) and whether it is predictive for postoperative cognitive dysfunction at 3 months (POCD). We enrolled 301 patients aged 65 or older and without signs of dementia who were undergoing elective surgery. Magnetic resonance imaging was conducted prior to surgery. Freesurf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this study, only male mice were used to investigate the role of SIRT1/BDNF in POCD. Although many studies have suggested that sex may not be a key factor affecting POCD [ 71 , 72 ], it is necessary to clarify whether the synaptic plasticity and neuronal excitability impairment mediated by SIRT1/BDNF downregulation were also the important cause of POCD in female mice. In addition, although the Golgi staining technique used in this study can directly observe the synaptic structural plasticity of neurons through microscopic images, its limitation is also obvious, since it randomly stains only a subset of neurons, providing a partial and unpredictable view of the overall neuronal population, potentially leading to incomplete or biased results.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only male mice were used to investigate the role of SIRT1/BDNF in POCD. Although many studies have suggested that sex may not be a key factor affecting POCD [ 71 , 72 ], it is necessary to clarify whether the synaptic plasticity and neuronal excitability impairment mediated by SIRT1/BDNF downregulation were also the important cause of POCD in female mice. In addition, although the Golgi staining technique used in this study can directly observe the synaptic structural plasticity of neurons through microscopic images, its limitation is also obvious, since it randomly stains only a subset of neurons, providing a partial and unpredictable view of the overall neuronal population, potentially leading to incomplete or biased results.…”
Section: Discussionmentioning
confidence: 99%